Gamma radiation dose rate measurements in granite quarries and schools in two mountainous towns in Benin (Brazilian Journal of Radiation Sciences (BJRS), 2024)
The radiation protection of the public against ionizing radiation emitted by natural sources from the earth's crust is a public health issue. The aim of this study, carried out in the granite quarries and schools of the towns of Glazoue and Dassa-zoume, is to assess the population's external exposure to ambient gamma radiation emitted by natural radionuclides (238U, 232Th, 40K, etc.). It covered the dry season from January to April 2021. 12 quarries and 39 schools were included in the study. 510 ambient gamma dose equivalent rates were carried out during the study period with the radiometer and the portable NaI gamma detector simultaneously. For comparison purposes, ten (10) measurements were taken in the city of Cotonou. Gamma dose equivalent rates in the quarries of both cities ranged from 0.11 to 0.40 µSv/h, with an average of 0.255 µSv/h. Those for primary and secondary schools vary from 0.08 to 0.40 µSv/h, with an average of 0.24 µSv/h. The average dose equivalent rate recorded at Cotonou is is 0.045 µSv/h. The effective dose for a resident crusher ranges from 1.10 to 2.80 mSv/yr, with an average of 2.10 mSv/yr. Those for non-resident crushers range from 0.6 to 1.4 mSv/yr. Those for schools range from 0.144 mSv/yr to 0.432 mSv/yr, with an average of 0.252 mSv/yr. The effective dose obtained for granite crushers is higher than the value mentioned in the 2008 UNSCEAR report for outdoors and indoors exposure to terrestrial and cosmic radiation, which is equal to 0.87 mSv/yr.